Congenital biotinidase deficiency – MRI findings in two cases - Ranjan, Rahul S; Taneja, Sunil; Singh, Anil; Gupta, Vikas (Indian Journal of Radiology and Imaging, 2019)
Congenital biotinidase deficiency is a rare inborn error of metabolism that most commonly presents in infantile age group. Diffusion changes on magnetic resonance imaging (MRI) are sparsely described in the literature. We are presenting diffusion-weighted MRI findings in two confirmed cases of congenital biotinidase deficiency in infantile age group with review of literature.
Keywords: Biotinidase deficiency; developmental delay; neurometabolic disorder; seizures